2017
DOI: 10.21149/7765
|View full text |Cite
|
Sign up to set email alerts
|

Tabaquismo en Costa Rica: susceptibilidad, consumo y dependencia

Abstract: Objetivo. Identificar elementos asociados con el taba­quismo, la susceptibilidad y la adicción en jóvenes de 13 a 15 años, para determinar condiciones de riesgo y posibles intervenciones desde las políticas sobre tabaco en Costa Rica. Material y métodos. Se utilizó información de las cuatro rondas de la Global Youth Tobacco Survey (GYTS) Costa Rica, con un tamaño muestral de 11 540 jóvenes colegiales. Se estimaron indicadores de interés y modelos de regresión logística para el consumo de tabaco, la susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Monge (2012) described the Costa Rican tobacco market and the implications of strict tobacco control on employment and consumption. Fonseca et al (2017) found that the susceptibility and prevalence of smoking have decreased, but also found an increase in the proportion of young people with tobacco addiction. Additionally, being a woman, and living with children under 15 years old or with older adults are factors that reduce the probability of consuming tobacco (Espinoza et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Monge (2012) described the Costa Rican tobacco market and the implications of strict tobacco control on employment and consumption. Fonseca et al (2017) found that the susceptibility and prevalence of smoking have decreased, but also found an increase in the proportion of young people with tobacco addiction. Additionally, being a woman, and living with children under 15 years old or with older adults are factors that reduce the probability of consuming tobacco (Espinoza et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%